Aplikasi Pemecahan Soal Sudoku dengan Metode Backtracking - Danuputri, Chyquitha; Santosa, Nico (Jurnal Informatika Universitas Pamulang, 2021)
In solving a puzzle requires dexterity, intelligence, and time depending on the difficulty of the puzzle to be solved, one of the popular puzzles is sudoku. This puzzle game often takes a long time to complete, especially at high difficulty levels. To solve puzzle problems more quickly and efficiently, a backtracking algorithm can be applied, which is a systematic logical sequence used to find a solution to a problem where there are several possible solutions. This research is meant to test the backtracking ability in solving sudoku problems at extreme difficulty levels and to test the speed of the backtracking algorithm in solving sudoku problems at extreme difficulty levels. In the application test, 20 questions were used and from testing the 20 questions, the accuracy rate of solving sudoku questions was 100%, while for the length of time for solving sudoku questions, the average length of time was 0.0880295 seconds. The application made is a desktop-based application made by Python programming language and PyGame library to create a user interface.